Pengaruh PLTB Sidrap Terhadap Sistem Kelistrikan Sulawesi Selatan - Riasa, I Putu; Hartati, Rukmi Sari; Manuaba, Ida Bagus Gede; Santiari, Dewa Ayu Sri (Majalah Ilmiah Teknologi Elektro, 2020)
New and renewable energy has become the green energy trend in the electric power system going forward. The Bayu Power Station (PLTB) is one of the centers of electricity generation with a primary source of energy that is pollution-free and environmentally friendly. Currently in the South Sulawesi system, PLTB has operated with a total power of 70 MW at a base load of around 700 MW. Because PLTB is very dependent on wind conditions, the power generated becomes unstable and this has a significant intermittent effect on the stability of the system. The results of this study indicate that the intermittent composition of nuclear power plants is increasing from the April-July 2018 period. This ever increasing contribution disrupts frequency stability in the South Sulawesi system